KORELASI ANTARA PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN PERILAKU KEAGAMAAN SISWA PADA MADRASAH ALIYAH NEGERI BANJARMASIN - M. Ramli (Jurnal Ilmiah Ilmu Pendidikan dan Kedakwahan, 2023)
After learning religious education taught in various schools, it is expected that students can obtain religious teachings properly and correctly with independent mastery. This could indicate that the learning achievement of Islamic religious education has a relationship with the religious behaviour of students. The type of research carried out in this case is field research with quantitative methods. The subjects of this study were students at several MANs throughout the city of Banjarmasin, namely MAN 1 Banjarmasin, MAN 2 Banjarmasin, and MAN 3 Banjarmasin, totaling 127 people. Data collection techniques were carried out by collecting documentation in the form of learning achievement data in the form of semester report cards on subjects namely, the Quran Hadith (QH), Islamic Cultural History (SKI), Fiqh, and Aqidah Akhlak (AA). Data on religious behaviour will be collected by giving a questionnaire consisting of 16 statements. The results show that the correlation between the learning achievements achieved by subjects in the PAI group and the religious behaviour of students at MAN throughout the city of Banjarmasin is very weak and tends to be uncorrelated, or there is no significant (non-significant) relationship between the variables of student achievement and religious behaviour. That is, it is not certain that students' excellent religious behaviour is the result or impact of their learning achievements, which are also very good in madrasas.